European Integration and the Future of Social Policy Making - Theodoros Iosifides; George Korres (European Regional Science Association (ERSA), 2005)
The basic aim of this paper is a brief presentation of the current situation as regards some central aspects of social policy formation and implementation in the European Union. The general rationale of the paper is the viewing of the European Union as one of the major global actors towards neoliberal globalization, resulting by the contemporary ideological and political dominance of certain social forces within it. The drive towards greater socio-economic liberalization, the emphasis on international competitiveness and the gradual commodification of previously considered public goods pose a remarkable threat to the European social model (or social models). The paper starts with a synoptic account of some crucial aspects of the contemporary social situation in the European Union (notably income distribution, unemployment, poverty and social exclusion) and of the most important social policy frameworks at European level. Subsequently the future prospects of the European social policy regime under the dominance of neoliberalism is discussed, opening new questions about the ways of reversing contemporary trends.
Keywords: 330